FACTORS AFFECTING EVENT ORGANIZER’S SERVICE PURCHASE INTENTION - Christianto, Joshua; Belgiawan, Prawira Fajar (Journal of Business and Management, 2018)
Abstract. As we know in Indonesia, Indonesia is home to more than a thousand tribes. Each tribe has a ritual to give meaning to the life phase, one of which holds a traditional ceremony ahead of maturity. Based on Indonesian regulation, 17 years old is a sign of maturity, it is shown from they able to have their own official ID from the country and also, they are now eligible to have their driving license. However, as the time goes by westernization occurred in Indonesia, westernization causing the fading of the original culture of a nation in a country, where a person or a group of people or nations is more capable of using or following western culture. Hence, because of westernization people tend to celebrate their maturity by throwing a sweet seventeen birthday party. In general, sweet seventeen event organizer is the one who manage the birthday party. Sweet seventeen event organizer is a term for professional service providers who basically have the main task of helping the client to be able to organize the event client wants. Booms and Bitner, was proposed an expanded marketing mix for services; product, price, place, and promotion and three additional elements: physical evidence, participants, and process. ThatÃ¢â‚¬â„¢s why using marketing mix in event organizer is essentials, since event organizer runs in service sector. Thus, this research is conducted to find which variable significantly influences the service purchase intention in using event organizer, in order to help event organizer to boost their sales. This research could be considered as exploratory quantitative study, because there was not any specific study that discuss about event organizer purchase intention. Quantitative approach by online questionnaire to 266 juveniles in Bandung is conducted. The researcher uses Ordinal Logistic Regression (OLR) in SPSS application to analyze the data. The result shows that Process, Physical Evidence, Promotion and Price are become the variables that proportionally and significantly affect event organizerÃ¢â‚¬â„¢s service purchase intention. Therefore, event organizer should improve the following factors in order to reach the market accurately that eventually will boost the sales, for the process factor, event organizer should keep an eye for itÃ¢â‚¬â„¢s good service through the process of arranging the event. For the promotion factor, event organizer should actively doing offline promotion and online promotion (through social Media: Instagram and LINE). For the physical evidence factor, customer is interested in event organizer that has a uniform while event, making conducive ambience on every event and has strict security. Lastly for the price, customer attracted to the event organizer that has various package. As for further research, research outside Bandung with bigger sample could be conducted to gain better understanding and knowledge about the factors affecting event orgnizerÃ¢â‚¬â„¢s service purchase intention.Keywords: Event Organizer, Marketing Mix, Purchase IntentionÃ‚Â Ã‚Â